Post a New Question

math

posted by .

Determine the equation of the function that has the indicated transformation applied to it.

f(x)= 3(x+1)^2-2

reflection across x-axis and stretched vertically by factor of 3

  • math -

    reflection: f(x)->-f(x) = -3(x+1)^2 - 2
    3 stretch: f(x)->3f(x) = 3(-3(x+1)^2 - 2)
    = -9(x+1)^2 - 6

  • math -

    oops
    -(3(x+1)^2 - 2) = -3(x+1)^2 + 2
    then stretch:
    -9(x+1)^2 + 6

  • math -

    Thanks

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question